Transforming nitrogen management of the urban food system in a food-sink city. (1st November 2019) - Huang, Wei; Gao, Bing; Huang, Yunfeng; Zhang, Zhiling; Xu, Su; Xu, Lilai; Cui, Shenghui
Abstract: Nitrogen flows in urban food systems are attracting increasing concern. However, characteristics of nitrogen flow and systematic measures to reduce reactive nitrogen losses in the food systems of consumption-oriented cities in developing countries have not been well understood, especially in a quantitative way. This study empirically investigates the transforming nitrogen flows of an urban food system in a food-sink city in China, with a nitrogen metabolism model. Three types of nitrogen loads transfer are identified: from production to consumption side, between different environmental media, and from areas within to areas beyond the city boundary. By integrating sensitivity analysis into the metabolism model, increases in the sewage treatment rate, the sewage nitrogen removal rate, and the ratio of animal excreta returned to field are found to contribute the most to the water nitrogen load reduction, and reducing food waste at the consumer level is the most influential measure for lowering soil nitrogen loads, under the existing nitrogen flow regime. Additionally, a three-tier template framework is proposed to streamline city strategies (prevention, abatement, recycling, regional cooperation, etc.) for reducing the N loads of urban food systems, providing references for sustainable nutrient management in urban ecosystems. Graphical abstract: Image 1 Highlights: Changing nitrogen flows of a food system in a food-sink city are investigated. Three types of nitrogen loads transfer are identified. Transforming management priorities in emerging food-sink cities are suggested. A three-tier framework is proposed to streamline urban mitigation strategies. The framework could provide a systematic approach to urban nutrient management.